Importance of Climate Change Adaptation in Drought Mitigation: A Review - Gana, A. H.; Sa’id, A. I. (UMYU Journal of Microbiology Research)
Climate change is an ongoing challenge that creates a range of environmental challenges that countries will have to grapple with in the coming decades. Droughts will definitely occur, but climate change has largely exacerbated hydrological trends, making droughts start more rapidly and more intensely. This study looked at the measures and tactics used in South Africa, Australia, Mexico, Spain, and the United States to lessen the effects of drought. Adapting to climate change offers an opportunity to rethink some of the outstanding issues of tragedy reduction and ecosystem growth. This helps mitigate future climate change impacts and embrace options for such adaptation to climate change. The main impacts of climate change on drought vulnerability are public-based awareness-raising, revised timeframes and drought forecasting approaches, improved preparedness with a focus on drought monitoring and the creation of early warning systems, and all similar preparations are combined at the input level. Moreover, reactive approaches to drought remain prevalent in many countries, despite emergency funding being expensive, ineffective and failing to address long-term sources of vulnerability and lack of support. There is therefore an urgent need for a paradigm shift from crisis management to risk management, adopting a proactive approach based on standard risk mitigation and prevention. Additional efforts to embed local adaptation strategies into policies may increase local resilience to environmental change while contributing to broader development goals.